Social dialogue during the financial and economic crisis. Results from the ILO/world Bank Inventory using a Boolean analysis on 44 countries - Baccaro, Lucio; Heeb, Stefan (Geneva, 2011)
"Using information collected by the ILO/WB Inventory of policy responses to the financial and economic crisis on 44 countries, this paper identified conditions under which there was a social dialogue response to the financial crisis between 2008 and 2010. For that purpose, they use a particular definition of social dialogue, e.g. the emergence of tripartite nationallevel agreements or major agreements at the sector level; and rely on a Boolean analysis, e.g. a statistical method to detect relationships between variables, for example between answers to a questionnaire. Based on this definition, 13 out of 44 countries adopted national level agreement or major sector level agreement in formulating their crisis response, including seven in Europe, three in Americas, two in Asia, and one in Africa. Explanatory factors for the emergence of social dialogue include freedom of association, the severity of the crisis, and the strength of trade unions."